Yusuf al-Qaradawi and Contribution of His Thoughts - Hasan, Z (Univ Sultan Azlan Shah, 2024)
Yusuf al-Qaradawi is one of the most influential and preeminent Muslim scholars in this contemporary time. He is known for his moderate views by his proponents and considered as a highly controversial Muslim scholar by his opponents. He is a well rounded scholar, as an intellectual leader, social activist, committed Muslim, prolific writer, Islamic activist and ex-member of the Muslim Brotherhood movement. Considering the significance of his intellectual thought to the general public, particularly Muslims all over the world including Malaysia, an analysis of Yusuf al-Qaradawi's influence and his contribution therefore offers an interesting and thoughtful discourse. In analysing Yusuf al-Qaradawi's intellectual thought and his contribution, this article discusses the concepts of renewal or tajdid, public intellectual, method of promoting the ideas, framework of Yusuf al-Qaradawi's intellectual thought and institutionalization of his ideas and thought.